EPISTAXIS AND ALLERGIC RHINITIS IN ATHLETES: PREVALENCE ACROSS SPORTS AND CONTEMPORARY MANAGEMENT STRATEGIES BASED ON LATEST EVIDENCE – A NARRATIVE REVIEW - Jakub Komorowski-Roszkiewicz; Wojciech Ługowski; Julia Samek; Karolina Bartoszewska; Iga Kwiecień; Karol Marcyś; Weronika Matwiejuk; Kamil Dziekoński (International Journal of Innovative Technologies in Social Science, 2025)
Purpose: This study aims to evaluate the prevalence of epistaxis and allergic rhinitis among athletes across different sports disciplines, and to review current management strategies based on recent clinical evidence. Materials and Methods: A comprehensive literature review was conducted, analyzing epidemiological data on epistaxis and allergic rhinitis incidence in various sports including contact, endurance, and outdoor disciplines. Management protocols were assessed with a focus on conservative, pharmacologic, and interventional treatments reported in randomized controlled trials and clinical guidelines. Results: Epistaxis was found to be more prevalent in contact sports such as boxing and rugby, predominantly due to trauma, whereas endurance and outdoor sports athletes experienced nosebleeds related to environmental dryness and mucosal irritation. Allergic rhinitis prevalence correlated strongly with exposure to allergens, particularly in outdoor sports during pollen seasons. Conservative management, including nasal compression and topical treatments, was effective in most anterior epistaxis cases. Cauterization and nasal packing remained standard for refractory bleeds, with newer hemostatic agents and tranexamic acid showing promising results. Allergic rhinitis was best managed through allergen avoidance, nasal saline irrigation, and intranasal corticosteroids, with combination antihistamine-corticosteroid sprays providing superior symptom control. Conclusions: Epistaxis and allergic rhinitis represent significant yet manageable health concerns in athletes, with prevalence influenced by sport type and environmental factors. Tailored, sport-specific management strategies improve outcomes and reduce performance disruptions. Further research into preventative measures and individualized therapies is warranted to enhance athlete care.